Transformation of Sequential Programs into Parallel Forms - Mohd Saman, Md. Yazid (Universiti Putra Malaysia Press, 1995)
One of the main tasks of a programmer when writing parallel programs is to identify the parts that are to be executed in parallel. This process is very time consuming and error prone. As an alternative, one can write its sequential version and then transform it into the parallel form by a parallelizing compiler. The loops in the sequential programs offer the best opportunities for parallelism. This paper presents the transformation techniques that can be applied to sequential programs, especially the loops, in order to parallelize them. These techniques are based on the Bernstein sets.